Fetal brain development in fetal growth restriction using MRI: a systematic review - L. Meijerink; I. M. van Ooijen; T. Alderliesten; F. Terstappen; M. J. N. L. Benders; M. N. Bekker (BMC Pregnancy and Childbirth)
Abstract Background This systematic review investigates potential differences in brain development between growth restricted (FGR)-fetuses compared to appropriate for gestational age (AGA) fetuses using MRI. Methods PubMed, Embase, Cochrane Library and Web of Science databases were searched from 1985 to 2023. FGR was defined as an estimated fetal weight (EFW) < p10 and/or an abdominal circumference (AC) < p10, or 20% reduction in EFW or AC using a minimum interval of two weeks. Outcomes included volumetrics, biometrics, apparent diffusion coefficients (ADC), 1H-MRS-metabolites, and oxygenation of the fetal brain. Risk of bias was assessed using Newcastle-Ottawa Scale (NOS). A meta-analysis was conducted on variables when reported in at least three studies, calculating the mean difference (MD) with a 95% confidence interval (CI). Results Twenty-nine studies were included after three-phase screening, 13 used the FGR consensus definition according to the Delphi procedure. Total brain volume and cerebellar volume were significantly reduced in FGR fetuses (n = 183; 74) when compared to AGA fetuses (n = 283; 166) with a MD of -30.84 cm3 (p < 0.01) and − 2.24 cm3 (p < 0.01). ADC values in the frontal white matter (FWM), occipital white matter (OWM), temporal white matter (TWM), thalami, centrum semiovale (CSO), basal ganglia, pons and cerebellum, significantly lower in growth restricted fetuses (-0.07 × 10–3 mm2/s (p < 0.01); -0.06 × 10–3 mm2/s (p < 0.01); -0.07 × 10–3 mm2/s (p < 0.01); -0.10 × 10–3 mm2/s (p < 0.01); -0.06 × 10–3 mm2/s (p < 0.01); -0.07 × 10–3 mm2/s (p < 0.01); -0.07 × 10–3 mm2/s (p < 0.01); -0.02 × 10–3 mm2/s (p < 0.01); respectively). 1H-MRS showed reduced levels of N-acetyl aspartate (NAA): Choline (Cho) and NAA: Creatine(CR) levels in the frontal lobe and central brain tissue, whilst contradictive findings concerning Cho: Cr and Inositol(Ino): Cho ratios were found. Two studies investigated the cerebral hemodynamic changes in FGR fetuses showing no difference in fractional moving blood volume, similar venous blood oxygenation in the superior sagittal sinus and no difference in T2* in the fetal brain. Discussion MRI provides additional information on fetal brain development in a growth restricted population. Smaller total brain and cerebellar volumes and lower ADC values in the FWM, OWM, TWM, thalami, CSO, basal ganglia, pons and cerebellum have been observed in FGR. These conclusions are drawn on relatively small sample sizes with high heterogeneity resulting from diverse study populations and MRI techniques. Furthermore, how these findings correlate to long-term neurocognitive abnormalities associated with FGR remains to be elucidated. A large cohort study comparing brain maturation, myelination, metabolic and hemodynamic status between brain-sparing FGR fetuses to healthy age-matched controls is needed.